Unveiling the impact of ICTs as a catalyst of technological innovation on well-being under gender inequality's moderating role - Cristina Boța-Avram; Viorela Ligia Vaidean; Monica Violeta Achim; Nawazish Mirza (Journal of Innovation & Knowledge (JIK), 2025)
Information and Communication Technologies (ICTs) represent a significant technological advancement that enhances communication, access to information, and socio-economic interactions. By analysing the impact of ICTs on well-being across nations, this study explores an essential aspect of technology innovation's role in improving individuals' overall quality of life - covering both subjective and objective well-being. This study aims to analyse the influence of ICTs on well-being while considering the moderating effect of gender inequality. The research uses panel data from 185 countries covering the years 2005 to 2021 to explore the relationship between ICTs and well-being concerning gender inequality, using both subjective (e.g., life satisfaction) and objective (e.g., prosperity) well-being indicators. The objective was to gain a deeper understanding of the complex relationship between ICTs and well-being, focusing on the moderating role of gender inequality. The findings suggest that there is a positive correlation between ICT impact and well-being, which is amplified as gender inequality decreases. These findings held consistent when using different measures of objective well-being and introducing new variables for comparison. The study offers valuable insights into the role of gender equality - an essential component of social innovation - in upholding the positive effects of ICTs on well-being, assessed from both subjective and objective perspectives.
Keywords: I31; O35; Q55; 650; ICT; happiness; Prosperity; Gender inequality; Subjective well-being; Objective well-being